Fuel molecular structure influences the polycyclic aromatic hydrocarbons formation of butanol/butane isomers: A ReaxFF molecular dynamics study. (15th February 2022) - Zhang, Pu; Wu, Hui; Song, Xueli; Liu, Yang; Cheng, Xiaobei
Highlights: ReaxFF MD study of PAHs formation pathway differences between butyl fuel isomers. The cleavage frequencies of C-C bond are related to the OH binding site. Differences in final decomposition products among isomers were revealed. Among the test fuels, t-butanol forms PAHs earliest at relatively lower temperature. T-butanol forms mono-aromatic rings earliest by dimerization between 2-methylallyl. Abstract: This work explores the influence differences in the molecular structure of butanol/butane isomers, particularly the hydroxyl (OH) group binding site, on polycyclic aromatic hydrocarbon (PAH) formation by using ReaxFF MD. Visualization of the fuel molecule decomposition and PAH formation processes revealed that OH bonded to interior carbon atoms could lead to earlier PAH formation onset in t-butanol and s-butanol. When OH groups were bonded to interior carbon atoms, these groups were easily abscised via simple fission, and the adjacent CC bonds showed less cleavage. Thus, abundant i-C4 Hx (2-methylallyl) species were detected from t-butanol with a branched carbon skeleton structure and specific OH binding sites. s-Butanol produced more n-C4 Hx species than t-butanol. Visualization of the formation of mono-aromatic ring molecules directly revealed that dehydrodimerization and dehydroaromatization by i-C4 Hx lead to the earliest onset of mono-aromatic ring formation in t-butanol. Mono-aromatic ring formation via cyclization and condensation by polyyne radicals occurred later in i-butanol than the upper pathway and dominated straight fuels at a higher temperature of 2500 K. The drastic decay of C2 H2 and visualization of HACA-like pathways in the simulation trajectories for n-butanol revealed the close concentration of the larger PAHs for straight-chain butanol isomers with the branched-chain isomers.